New insights on the latest Messinian-to-Piacenzian stratigraphic series from the Dahra Massif (Lower Chelif Basin, Algeria): Lago Mare, reflooding and bio-events - Atik Asma; Mansouri Mohamed El Habib; Bessedik Mostefa; Osman Mohammed Kamel; Belkebir Lahcene; Saint Martin Jean-Paul; Chaix Christian; Belkhir Ayoub; Gorini Christian; Belhadji Ahmed; Satour Linda (BSGF - Earth Sciences Bulletin, 2024)
Geological investigations carried out on the Dahra Massif have revealed sedimentary changes and bioevents characterizing the post-gypsum detrital sediments (from Messinian to Piacenzian), which are followed by the Trubi equivalent Pliocene marls or white marly limestones. Structured into two superimposed steps, the late Messinian deposits yielded two successive ostracod assemblages. They indicate a brackish environment for the lower and a fairly open shallow brackish environment for the second. Based on their ostracod content, assemblage 1 (Cyprideis, Loxoconcha muelleri) corresponds to the Lago Mare biofacies 1 of the Apennine foredeep, which is correlated with the Lago Mare 1 episode dated between 5.64 and 5.60 Ma. Assemblage 2 (Loxocorniculina djafarovi) is referred to the Lago Mare biofacies 2 described in the same region. It is correlated with the Lago Mare 3 episode, dated between 5.46 and 5.33 Ma. Moreover, the stratigraphic succession is marked by a major discontinuity indicated by a hardground, separating step 1 from step 2 and corresponding to the ostracod assemblages 1 and 2, respectively. This discontinuity is considered here to be equivalent to the Messinian Erosional Surface, already evidenced in the region and widely known around the Mediterranean Basin. These late Messinian deposits and their ostracod assemblage 2, notably the detrital sedimentation with Ceratolithus acutus, Globorotalia margaritae, Reticulofenestra cisnerosii document a marine incursion into the Lower Chelif Basin, corresponding to the latest Messinian marine reflooding of the Mediterranean Basin, that happened before the earliest Zanclean R. cisnerosii occurrence. Finally, the bioevents evidenced in the Dahra Massif, reinforce the evidence of the late Messinian Lago Mare 3 episode, and support the ante-Zanclean age of the marine reflooding of the Mediterranean. The overlying deposits are marked by coral constructions (cf. Cladocora cf. caespitosa, Dendrophyllia sp) never described before and covering the entire early Zanclean, testifying the existence, at that time, of warm enough conditions, which may correspond to the marine isotopic stage TG5.